The Role of Waqf in Financing Religious Social Activities in North Labuhanbatu Regency - Syahnan Syahnan; Syafruddin Syam; Ali Saat Husaini Siregar (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
The most important problem that is so easy to see is the problem of understanding and knowledge about waqf, both those who are waqf and those who manage the waqf. So far, those who do waqf only understand that waqf is only a worship whose reward will flow continuously without limit. This type of research is field research and juridical normative. In order to obtain answers from this research, the researchers conducted direct research in North Labuhanbatu Regency. The primary data from this study are waqf data originating from the Ministry of Religion of North Labuhanbatu Regency, KUA throughout North Labuhanbatu Regency and those from waqf nazirs in North Labuhanbatu Regency. In addition, secondary data sources are Law No. 41 of 2004 concerning Waqf, Government Regulation No. 42 of 2006 concerning the Implementation of Law no. 41 of 2004, books related to research. This study explains whether waqf in North Labuhanbatu Regency has a role or not in helping finance social activities. Then explain the application of Law No. 41 of 2004 concerning Waqf in North Labuhanbatu Regency. There are three research questions that are answered in this study, including those related to waqf institutions in North Labuhanbatu Regency in terms of Law no. 41 of 2004 concerning Waqf. Then about the procurement and management process of waqf in financing social activities in North Labuhanbatu Regency. Then in North Labuhanbatu Regency there is no BWI representative. So that the waqf there is managed by waqf nazirs who are legalized by the existence of the Waqf Pledge Deed (AIW) issued by the Head of the District Office of Religious Affairs. None of the waqf nazir has been approved by the Indonesian Waqf Board.